Using Non-Textual Sources : A Historian's Guide - Armstrong, Catherine (Bloomsbury Research Skills for History Ser, 2015)
Cover -- Contents -- List of Illustrations -- Introduction -- 1 Borrowing from Other Disciplines -- 2 Reading Images -- 3 Film, TV and Audio Sources -- 4 Material Culture and the Built Environment -- 5 Practical Applications -- Notes -- Bibliography -- Index.